The Role of Internal Auditors in Ensuring Effective Financial Control at County Government Level: The Case of Trans Nzoia County, Kenya. - W. Chesoli, Dr. Joshua (IJRDO - Journal of Business Management, 2017)
This paper assesses the role of internal auditors in ensuring effective financial control at County government level, a case of Trans Nzoia County. The methodology employed for data collection is only primary source, which involved the use of questionnaires, in which 50 questionnaire were administered to the staff of Accounting and Internal audit department of Trans Nzoia County, out of which only 35 questionnaires were completed and returned. The data generated for the study were interpreted using simple percentage. The main finding of the study include among other; lack of proper independent exercise by the internal auditor, understaffing in the side of internal audit unit, the internal control system is very weak toward financial and other controls and also non adherence by the auditors on general auditing standard. The paper recommends that internal auditors should exercise the degree of independency on various department within the organisation in performing their duties, the internal control system should be efficient in such away that it will prevent any act of financial crime and detection of fraud and County government should established a scheme for internal auditors training from time to time because it will enhances there operational capacities and skills in administering the internal control system by way of attending professional seminars, workshop and symposium